Calculation of Prayer Times in the Book al-Durus al-Falakiyyah - Alfan Maghfuri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
Determination of prayer times in al-Durus al-Falakiyyah uses a list of logarithms with 5 decimals. The existence of this logarithmic list is now very difficult to find, and what is circulating today is a list of logarithms with 4 decimal places and 3 decimal places. If the list of logarithms is used, it will certainly bring up the difference from the original calculation. This study attempts to answer the question whether the list of decimal 4 and 3 decimal places is appropriate for the reckoning of prayer in al-Durus al-Falakiyyah as a substitute for a list of 5 decimal logarithms. An assessment of its feasibility can be seen from whether or not the difference arising from the original calculation can be ignored or not. The results showed that the use of a list of 4 decimal logarithms raises a very small difference, which is an average of 1.12 seconds, so that the difference can be ignored when rounded. But to use a logarithmic decimal 3 list, the difference that is raised can reach 52 seconds. The difference cannot be ignored when rounded and can change the results of the original calculation.